Hop Harvesting Procedures for Small-Scale Production - Shinsuke Agehara; Christopher DelCastillo; Mariel Gallardo; Weining Wang; Jack Rechcigl (EDIS)
This new 4-page publication of the UF/IFAS Horticultural Sciences Department explains hop harvesting procedures for small-scale production (generally up to 5 acres). It is part of a series that examines the challenges and opportunities for hop production in Florida based on research at the UF/IFAS Gulf Coast Research and Education Center. Written by Shinsuke Agehara, Chris DelCastillo, Mariel Gallardo, Weining Wang, and Jack Rechcigl. https://edis.ifas.ufl.edu/hs1437